Validity and reliability of the solidarity in pandemics scale - ULUMAN MERT, MÜGE; ERYİĞİT, DERYA (My University, 2021)
This study developed a measure of solidarity levels during pandemics, the Solidarity in Pandemics Scale (SPS). This was achieved using a study group of 842 individuals aged between 18 and 65 from different segments of society who had experienced the COVID-19 pandemic and differed in age, gender, and socioeconomic status. Exploratory factor analysis was used to establish the construct validity of the scale, producing a 15-item scale with a one-dimensional structure that explained 34.36% of the variance. Confirmatory factor analysis using a different study group revealed that all items have significant t-values, and the model established according to model fit indexes has meaningful and acceptable fit values. The internal consistency of the scale results was calculated using the Cronbach Alpha coefficient, and a reliability of .85 in terms of internal consistency was obtained. Test-retest reliability results as another indicator of reliability were found to be .85. Scores on the Altruism Scale were compared with those on the SPS to evaluate the scale’s criterion validity, and a significant relationship was found between the two scale scores. This analysis indicates that the Solidarity in Pandemics Scale is a valid and reliable psychometric tool.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Solidarity; pandemics; solidarity in pandemics; scale development; validity; reliability